Duration of untreated psychosis and acute remission of negative symptoms in a South American first‐episode psychosis cohort. Issue 1 (9th August 2015) - González‐Valderrama, Alfonso; Castañeda, Carmen Paz; Mena, Cristián; Undurraga, Juan; Mondaca, Pilar; Yañez, Matías; Bedregal, Paula; Nachar, Ruben
Abstract: Aim: To determine the association between duration of untreated psychosis (DUP) and symptoms remission in a hospitalized first‐episode psychosis cohort. Methods: Inpatients with a first‐episode non‐affective psychosis were recruited. Subjects were divided into two groups of long and short DUP using a 3‐month cut‐off point, and this was related to remission at 10 weeks of treatment. Multivariate analyses were performed. Results: Fifty‐five inpatients were included. There were no differences in remission rates of positive symptoms. Up to 76.5% of the patients with a short DUP (<3 months) achieved remission of negative symptoms versus 31.6% in the DUP ≥ 3 months group ( P  = 0.003). After controlling for relevant factors, patients with a shorter DUP were still three times more likely to achieve negative symptoms remission (HR: 3.04, 95% CI 1.2–7.5). Conclusions: DUP is a prognostic factor that should be considered at an early stage to identify a 'high risk' subgroup of persistent negative symptoms.